Relationship between circulating inflammatory factors and glioma risk and prognosis: A meta‐analysis - Yuan Feng; Jia Wang; Dezhong Tan; Peng Cheng; Anhua Wu (Cancer Medicine, 2019)
Abstract Background Inflammatory factors have been considered a significant factor contributing to the development and progression of glioma. However, the relationship between circulating inflammatory factors and glioma risk as well as their prognostic values in glioma patients is still inconclusive. Here, we performed a meta‐analysis to address this issue. Methods Relevant articles were identified through PubMed, EMBASE, the Cochrane Library, Web of Science, Wanfang database, and China National Knowledge Infrastructure (CNKI) from inception to February 2019. The weighted mean differences (WMDs) or standard mean differences (SMDs) with 95% confidence intervals (CIs) were used to describe the predictive ability of the levels of circulating inflammatory factors on glioma risk. To evaluate the prognostic values of the circulating inflammatory factors in glioma, hazard ratios (HRs) with 95% CIs were used. Results Thirty‐one studies comprising 2587 patients were included. The overall analysis showed that increased circulating interleukin‐6 (IL‐6) [SMD 0.81 (95% CI: 0.21‐1.40; P = .008)], interleukin‐8 (IL‐8) [SMD 1.01 (95% CI: 0.17‐1.84; P = .018)], interleukin‐17 (IL‐17) [SMD 1.12 (95% CI: 0.26‐1.98; P = .011)], tumor necrosis factor‐α (TNF‐α) [SMD 1.80 (95% CI: 1.03‐2.56; P = .000)], transforming growth factor‐β (TGF‐β) [SMD 10.55 (95% CI: 5.59‐15.51; P = .000)], and C‐reactive protein (CRP) [SMD 0.95 (95% CI: 0.75‐1.15; P = .000)] levels were significantly associated with glioma risk. On the other hand, our results showed that circulating IL‐6 [HR 1.10 (95% CI: 1.05‐1.16; P = .000)] and CRP [HR 2.02 (95% CI: 1.52‐2.68; P = .000)] levels were highly correlated with a poor overall survival (OS) rate in glioma patients. Conclusion Our results indicate that increased circulating IL‐6, IL‐8, IL‐17, TNF‐α, TGF‐β, and CRP levels are significantly associated with increased glioma risk. Moreover, our meta‐analysis suggests that circulating IL‐6 and CRP may serve as powerful biomarkers for a poor prognosis in glioma patients.